(untitled) (Journal of Universal Science Research, 2024)
This article discusses the development of a program in Python to analyze the structure of a website using the parsing method. The work presents the developed algorithm for the program, describes the software and conducts experiments on web site parsing. The program’s algorithm includes sending a GET request to a website, receiving and analyzing the HTML code of the page using the BeautifulSoup library. The find_all(’a’) method was used to analyze the website structure and extract link information. The obtained data was processed and displayed in a convenient format. It allows you to automate the process of analyzing the structure of a website, which can be useful for web developers, SEO specialists and web resource owners.